Analysis of Bank Financial Health Level Based on The Camel Method (Case Study of BPR Eka Dana Mandiri in Malang City for 2020-2022 Period) - Sisilia Stefani Jaya; Cakti Indra Gunawan; R Y Susanto (International Journal of Management and Business, 2026)
PT BPR Eka Dana Mandiri is a conventional banking business entity. It was founded in 1971 under the name PT Bank Pasar Bhirawa and is located in Bangil, Pasuruan. When its business activities were underway, Bank Pasar Bhirawa received administrative sanctions from Bank Indonesia in the form of a frozen business activity (BBKU). Then, on August 30, 2002, the Deputy Governor of BI issued a decree revoking the status of Frozen Business Activity Bank (BBKU) for Bank Pasar Bhirawa. One of the efforts made to revoke the BBKU was through an acquisition process by new investors. This study aims to analyze the financial health level of PT. BPR Eka Dana Mandiri in Malang City for the 2020-2022 period based on the CAMEL method which includes aspects of Capital, Asset Quality, Management, Earnings, and Liquidity. The research method used is quantitative descriptive research using data from the bank's annual financial reports for the 2020-2022 period. The data analysis technique was carried out by calculating financial ratios included in the CAMEL method, namely the Capital Adequacy Ratio (CAR), Productive Asset Quality (KAP), Net Profit Margin (NPM), Return on Assets (ROA), BOPO (Operating Costs to Operating Income), and Loan to Deposit Ratio (LDR), then compared with the assessment standards set by Bank Indonesia. The results showed that in general, the health level of PT. BPR Eka Dana Mandiri during the 2022-2022 period was in the healthy category based on the CAMEL composite rating. The capital aspect, as measured by CAR, indicated a very healthy condition because it was above the established minimum standard. The asset quality aspect, as measured by KAP, indicated a controlled condition. The management aspect in generating profits was quite good. From the earnings aspect, the ROA and BOPO ratios indicated efficient profitability performance. Meanwhile, the liquidity aspect, as measured by LDR, indicated the bank's ability to meet its short-term obligations properly.